Modelación del coeficiente de rugosidad de Hazen-Williams para tuberías de acero negro en el cálculo de las pérdidas de presión en sistemas hidráulicos de redes ramificadas - Defaz Chimba, Jessica Belén (2021)
There are several mathematical models that make it possible to determine the pressure loss in hydraulic networks of fire-fighting systems, each of them with a certain calculation precision. Part of the Ecuadorian regulation of fire extinction and mitigation is based on the NFPA (National Fire Protection Association) standards, which recommend the use of the Hazen-Williams method for said calculation, although it is true, this method is simple, fast and easy. to use, but inaccurate due to its limited range of Hazen-Williams roughness coefficients. Therefore, in this investigative work the modeling of the roughness coefficient of Hazen - Williams is presented as a function of the Reynolds number, diameter and the roughness of the material for ASTM A53 steel pipes, with the aim of reducing errors in the determination of pressure losses in hydraulic systems of branched networks. This modeling has allowed us to verify that the Hazen – Williams coefficient changes depending on the flow and material conditions. When comparing the pressure losses due to friction obtained as a function of the modeled coefficients, with other methods such as the experimental model and the Darcy – Weisbach model, a minimum difference has been reached in the calculation of the losses .